A state-of-the-art review of concrete strength detection/monitoring methods: With special emphasis on PZT transducers. (2nd January 2023) - Ji, Yanting; Chen, Aijiu; Chen, Yu; Han, Xiaoyan; Li, Bin; Gao, Yujia; Liu, Chuang; Xie, Jingzhou
Highlights: Detection/monitoring of concrete strength mainly includes micro-destructive and non-destructive methods. Technical characteristics, advantages, disadvantages, and applicable scenarios of methods are considered. The PZT transducers are connected with concrete by surface bonding or embedding. The difficulties in the application of PZT transducers in engineering are revealed. Abstract: Concrete is the most widely used building material in civil infrastructure, and strength is the most effective evaluation index to measure its quality. Sub-standard raw materials, flawed construction operations, and harsh construction environments can cause concrete to fail to meet the relevant technical strength requirements, and may even induce major engineering accidents. Therefore, using real-time detection/monitoring of concrete strength during construction could provide timely insights into the appropriateness of its strength development, ensure the safety and stability of structures, and thus avoid casualties and economic losses. In recent years, with the advancement of new materials, novel processes, and electronic information technology, innovative strength detection/monitoring technologies have been proposed. These methods have mainly been classified as (a) micro-destructive methods and (b) non-destructive methods. This paper provides a state-of-the-art review of the various detection/monitoring methods of concrete strength, including the core drilling method, pull-out method, pull-off method, nail shooting method, rebound method, ultrasonic pulse velocity (UPV) method, ultrasonic-rebound method, electromechanical impedance (EMI) method, and wave propagation (WP) method. The technical features, advantages, drawbacks, and applicable scenarios of each method are summarized to provide the basis for method selection. In addition, the EMI method and WP method based on lead zirconate titanate (PZT) are highlighted. Both methods embed PZT transducers into concrete or bond them with the surface to monitor online the strength development of a concrete structure in real-time. They offer the advantages of efficient monitoring, operational convenience, and cost-saving, and are new trends in concrete strength monitoring.